2019
DOI: 10.1111/ggi.13837
|View full text |Cite
|
Sign up to set email alerts
|

Japanese older adults’ loneliness, family relationships and mortality: Does one's living arrangement make a difference?

Abstract: Aim: This study examines how the association between older adults' family relationships and all-cause mortality differs among different household contexts: living alone, living with only a spouse and living with adult children.Methods: We carried out a discrete-time event history analysis on all-cause mortality with measures of family relationships for each group of older adults. The study analyzed personwave data from the Nihon University Japanese Longitudinal Study of Aging, including 11 225 longitudinal epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Healthcare professionals who participated in this study understood that there was a higher level of loneliness in older adults' homes than in care homes [29,30], contrary to what other studies have demonstrated [22,32]. Irrespective of the context in which the older adults lived, and even being surrounded by many people, if they did not have the support and company of their loved ones, this generated negative and unpleasant feelings [30,32,66]. This, coupled with boredom and the monotony of daily life, led to feelings of loneliness [24,31,34].…”
Section: Discussionmentioning
confidence: 63%
“…Healthcare professionals who participated in this study understood that there was a higher level of loneliness in older adults' homes than in care homes [29,30], contrary to what other studies have demonstrated [22,32]. Irrespective of the context in which the older adults lived, and even being surrounded by many people, if they did not have the support and company of their loved ones, this generated negative and unpleasant feelings [30,32,66]. This, coupled with boredom and the monotony of daily life, led to feelings of loneliness [24,31,34].…”
Section: Discussionmentioning
confidence: 63%
“…According to a previous Japanese study, the percentage of individuals experiencing loneliness among those aged 65 and above who were living with a spouse only, living with children, and living alone was 17.7%, 18.5%, and 37.3%, respectively. 26 The lower incidence of loneliness in the present study may reflect the fact that working-age individuals more actively participate in society through work, and are in the early stages of marriage and raising children. However, we found that workers who were unmarried, divorced, or had lost a partner; had no neighbors or friends to talk, ask for favors, or communicate with on social networking sites; had little time to spend with family, or ate meals alone tended to feel lonely despite working.…”
Section: What Is Already Known On This Topicmentioning
confidence: 57%
“…According to a previous Japanese study, the percentage of individuals experiencing loneliness among those aged 65 and above who were living with a spouse only, living with children, and living alone was 17.7%, 18.5%, and 37.3%, respectively. 26 The lower incidence of loneliness in the present study may reflect the fact that working-age individuals more actively participate in society through work, and are in the early stages All rights reserved. No reuse allowed without permission.…”
Section: What Is Already Known On This Topicmentioning
confidence: 73%
“…Sons/daughters and spouses were the primary informational providers and accounted for a higher proportion. However, older adults who lived with family members predicted a decline in functional status, due to their lack of knowledge of disease perception (Takagi & Saito, 2020). Family members were short of communication and connection with professional staff in transitional care (Pohontsch et al, 2018), multidisciplinary collaboration needed considering and keeping diverse information flowing (Hirschman et al, 2017; Figure 1a).…”
Section: Current Situation Of Informational Support Of Transitional Care For Older Adults With Chronic Diseasesmentioning
confidence: 99%